Analysis of working nanofluids for a refrigeration system (2016)
This paper presents the analysis of nanorefrigerant fluids to improve the thermal efficiency of a refrigeration system. Simulations in ANSYS FLUENT 15.0 were performed with mixtures of refrigerants R113, R123 and R134a, with Al2O3 nanoparticles at 1 vf% and 5 vf% (vf%, fraction volume concentration), flowing through a horizontal tube with a constant wall temperature. A mixture and the k-e turbulent models were employed to obtain results of heat transfer coefficient, temperature and pressure drop for each case. Results show an increment in thermal characteristics by adding 1 vf% and 5 vf% of Al2O3 nanoparticles to the three refrigerants selected. However, the size of the nanoparticle does not affect the thermal properties of nanofluid and the pressure drop does not show a specific pattern of behavior at different concentrations of nanoparticles. Finally, the mixture of R134a with 30 nm of mean diameter size Al2O3 at 1 vf% was selected because of its higher thermal efficiency and its favorable properties as a refrigerant.